A 61-Years-Old Female with Moyamoya Syndrome: A Case Report - Martha Oktavia Dewi Savitri; Azmi Farah Fairuzya; Subandi; Iqbal Imanuddin; Andry Nur Wahyu Putra Romadhoni; Tomohiro Hosoya (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2025)
Background: Moyamoya vasculopathy (MMV), like Moyamoya disease (MMD) and Moyamoya syndrome (MMS), is a rare chronic cerebrovascular angiopathy, especially in elderly patients. The incidence onset of MMV were unique with bimodal peak age: 5-10 years old and 25-49 years old. Case: A 61-year-old-female complaint of sudden onset left-sided hemiparesis one month before admission, headache, and forgetfulness. She had history of diabetes mellitus for 3 years. Neurological physical examination found left hemiparesis with motoric strength 4/5. Laboratory findings are unremarkable. Brain MRI with contrast showed infarcts at subcortical regions. Her cerebral DSA examination suggested diffuse multiple stenosis in the anterior circulation and total occlusion of left external and internal carotid artery. “Puff of smoke” and “champagne-bottle like neck sign” were found in DSA imaging, typical signs of MMD. She received aspirin 80 mg as her secondary prevention of another stroke event. Discussion: MMV case at elderly onset which is similar to prior small study with mean age of 60 years old. Previous study mentioned hypertension (44%) and diabetes mellitus (16%) were found in older MMD patients. Patient was given aspirin 80mg daily. Precautions in this case include taking lifelong antiplatelet, managing diabetes mellitus, and implementing lifestyle modification. This treatment approach was directed to lower concomitant risk of ischemic stroke. Conclusion: We report a case of MMV which was considered as a rare case and a cause of stroke event. The management of this case was directed to control the coexisting condition of ischemic stroke using antiplatelet drug and risk factor management.